HUBUNGAN STATUS GIZI, KEBIASAAN SARAPAN, DAN POLA TIDUR DENGAN INDEKS PRESTASI KUMULATIF MAHASISWA PROGRAM STUDI GIZI ANGKATAN 2019 DAN 2020 UPN VETERAN JAKARTA - Farah Devina Ramadhianti (2022)
Grade Point Average (GPA) is a tool to measure academic achievement. Academic achievement can be influenced by nutritional status, breakfast habits, and sleep patterns. Maintaining breakfast habit every day helps the body to get enough nutrients in order to achieve normal nutritional status. This supports brain development and work productivity that affects academic achievement. Bad sleep patterns can result in fatigue and drowsiness that can result in bad concentration and cause bad academic achievement. This study aims to determine the relationship between nutritional status, breakfast habits, and sleep patterns with the GPA score of the Nutrition students of UPN Veteran Jakarta. This study is an observational analytic study using a cross sectional design of 72 respondent with purposive sampling technique. The population are students of the 2019 and 2020 Nutrition study program. Data were collected using online questionnaires. The results showed that the majority of respondents had good nutritional status, breakfast habits, and sleep patterns. The statistical test of this study used the Chi-Square test. The results of statistical tests showed that there was a relationship between nutritional status (p value = 0.001) and sleep patterns (p value = 0.027) with GPA. However, there is no relationship between breakfast habits and GPA (p value = 0.832).